Jus Cogens Pro Homine: : Considerations on a special category of norms of protection of the human person - Marques, Miguel (Revista de Direito Internacional e Globalização Econômica, 2022)
Objectives: This paper aims to analyze some norms of protection of the human person, called jus cogens pro homine or pro persona, due to their specificities. Methodology: The inductive approach study was carried out through the understanding of legal concepts and extensive bibliographic research, with an exploratory and conclusive objective. Results: The study concludes that jus cogens involves a set of norms covering the international community, States and individuals. Jus cogens pro homine or pro persona, inserted in the last field, contains a special category of the norms of protection of the human person. Contributions: It is an extremely relevant discussion, which helps to define the scope of action of international jus cogens.